Modelling code mobility and migration: an OPM/Web approach. (25th July 2005) - Reinhartz-Berger, Iris; Dori, Dov; Katz, Shmuel
Web applications exhibit dynamic behaviour through such features as animation, rapidly changing presentations, and interactive forms. The growing complexity of web applications requires a rigorous modelling approach capable of clearly and explicitly addressing code mobility issues. While mobile agent systems and programming languages support the implementation of code mobility with features such as applets or mobile agents, existing system analysis and design methods lack the facilities to model code mobility satisfactorily. OPM/Web is an extension of object-process methodology (OPM) for modelling distributed systems and web applications that enables intuitive modelling of code mobility concepts in a single framework. We propose generic OPM/Web models for common code mobility design paradigms, including Remote Evaluation, Code-on-Demand, PUSH and Mobile Agents. An OPM/Web model of a mobile application that handles requests for Quality of Service over the internet exemplifies the use and advantages of modelling such systems in OPM/Web.